Actual problems of detection and disclosure of criminal offenses committed on the Internet - Imangaliyev, Н.К.; Temirzhanova, Л.А. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2022)
The article examines the problematic issues of identifying and countering criminal offenses committed on the Internet. Analysis of statistical data indicates a significant increase in this type of offenses. The main share of crimes remains unsolved due to the lack of access to stored information on the use of information systems in the databases of Internet providers, social networks and other organizations. In most cases, the attackers are located outside the country where the stolen funds are transferred. The procedural requirements imposed by the legislator do not allow prompt access to them, which entails the loss of evidence, complicates the search for criminals and stolen funds. The author formulated proposals for improving domestic legislation aimed at strengthening public policy measures in terms of protecting the constitutional rights of citizens.